Foreign Trade and Integration Policy: Eurasian Economic Union - Dashkhuu, Batmunkh (Mongolian Journal of Strategic Studies, 2025)
In recent years, international trade has been characterized by uncertainty due to geopolitical conflicts, and countries have increasingly focused on bilateral and cross-border trade. While the globalization process was directed towards the old major centers, the process of fragmentation of inter national trade has become more concentrated, focusing on cross-border and regional trade. In this context, the establishment of an interim free trade agreement with the Eurasian Economic Union is a manifestation of our country’s focus on regional cooperation to develop foreign trade and integration. In addition, Mongolian President Ukhnaagiin Khurelsukh, made an official visit to Central Asia countries, expending trade and economic cooperation in the region and taking important steps to develop regional integration. Therefore, this research work is aimed at studying the advantage and disadvantage of free trade experiments related to the economic activities of Eurasia in the development of foreign trade and integration, and identifying the problems in ensuring the security of the interests of our country. According to the results of the study, our country’s signing the free trade agreement with the Eurasian Economic Union will be beneficial in the long-term but will be a negative impact on domestic food production in the short term. Гадаад худалдаа, интеграцын бодлого: Евроазийн эдийн засгийн холбоо Хураангуй: Олон улсын худалдаанд сүүлийн жилүүдэд геополитикийн зөрчилдөөнөөс үүдэлтэй тодорхой бус байдал үүсэж, улс орнууд хоёр талт болон хил орчмын худалдаанд түлхүү анхаарал хандуулах болов. Даяарших үйл явц хуучин том төвүүд рүү чиглэсэн бол өдгөө хил залгаа улс хоорондын болон бүс нутгийн худалдаанд анхаарал хандуулж дангаарших үйл явц илүү түгэх болов. Энэ нөхцөлд манай улс гадаад худалдаа, интеграцыг хөгжүүлэхийн тулд бүс нутгийн хамтын ажиллагаанд анхаарал хандуулж буй илрэл нь Евроазийн эдийн засгийн холбоотой чөлөөт худалдааны түр хэлэлцээр байгуулах явдал юм. Мөн Монгол Улсын Ерөнхийлөгч У.Хүрэлсүх Төв Азийн орнуудад албан ёсны айлчлал хийж, тус бүс нутгийн худалдаа, эдийн засгийн хамтын ажиллагааг өргөжүүлж, бүс нутгийн интеграцыг хөгжүүлэхэд чухал алхмуудыг хийсэн. Иймд энэхүү судалгааны хүрээнд гадаад худалдаа, интеграцыг хөгжүүлэхэд Евроазийн эдийн засгийн холбоотой байгуулах чөлөөт худалдааны хэлэлцээрийн давуу болон сул талуудыг судалж, өөрийн улсын эрх ашиг аюулгүй байдлыг хангахад ямар асуудал байгааг авч үзлээ. Судалгааны үр дүнгээс үзвэл Евроазийн эдийн засгийн холбоотой манай улс чөлөөт худалдааны хэлэлцээр байгуулснаар урт хугацаанд ашигтай бөгөөд богино хугацаанд дотоодын хүнсний үйлдвэрлэлд сөрөг нөлөөтэй байна. Түлхүүр үг: Эдийн засгийн аюулгүй байдал, хэлэлцээр, экспорт, импорт, тариф